IMPLEMENTASI PEMBELAJARAN HYBRID PADA MATA KULIAH PENULISAN KARYA TULIS ILMIAH (PKTI) PADA KELAS PAI DI IAIN KUDUS - Asror, Fuad Mafatichul (Institut Islam Nahdlatul Ulama Temanggung, 2022)
Indonesia has begun to change the status of the covid 19 pandemic to endemic covid 19. In mid-March 2022 the Minister of Health in Indonesia announced that Indonesia had entered a transition from pandemic to endemic. This change is due to the decreasing number of pandemic indicators and the lower rate of transmission of COVID-19. During the pandemic, learning has been carried out online. Several universities have implemented hybrid learning, including IAIN Kudus. Online learning is carried out using media including zoom meetings, google meet, and others. This study used a qualitative - descriptive approach, and data collection was carried out by observation and documentation. In this study, several obstacles were found as a result of this research, namely, in hybrid learning in the Scientific Writing (PKTI) course in the PAI class, using zoom media with the hybrid method became less effective because the concentration was divided from the teacher to students who were present in on-campus classrooms and students using zoom off-campus, resulting in a lack of productive interaction between teachers and students. From the research findings here, suggestions for further researchers evaluate or analyze so that learning in PKTI courses can run conducive and productive.